Development of Interactive Learning Media for Vocational High Schools in Basic Computer Network and Telecommunication Engineering Subjects - Chandra Hannafi Atsna; Puspanda Hatta; Yusfia Hafid Aristyagama (Informatics Education Department, Faculty of Teacher Training and Education, Universitas Sebelas Maret, 2025)
The development of technology in the Industry 4.0 era has brought significant changes in many aspects of life, including our education. In the formal education system, teachers play a crucial role in creating an engaging and effective learning environment. This research aims to develop an interactive learning media called Comneter (Computer Network Learning) as a learning media to help students with their understanding of basic computer networks and telecommunication in vocational high schools. Comneter was developed using Unity software, a cross-platform game engine that enables us to create apps for both mobile and desktop platforms. The method used for this research is the Research and Development (R&D) method, with ADDIE (Dick et al., 1996) as the model of this development. This model consists of 5 main phases, including analysis, design, development, implementation, and evaluation. The results from this research show that Comneter received a feasibility assessment from a material expert, a media expert, students, and a teacher (as a respondent), with an average score of 3.96, categorizing Comneter as ‘Good’ or feasible. Therefore, it can be concluded that, based on this research, using computers can help enhance students’ comprehension in basic computer network and telecommunications engineering subjects, and has the potential to be used in vocational high schools to create a more effective and engaging learning experience